Characterization of the biofilm grown on 304L stainless steel in urban wastewaters: extracellular polymeric substances (EPS) and bacterial consortia. Issue 8 (13th September 2020) - Ziadi, Islem; El-Bassi, Leila; Bousselmi, Latifa; Akrout, Hanene
Abstract: Characterization of the biofilm growing on stainless steel (SS) in untreated (UTUWW) and treated (TUWW) urban wastewaters was performed. In both media, the first phase of biofilm growth was aerobic, when the genera Caldimonas, Caulobacter, Terriglobus and Edaphobacter (iron oxidizing bacteria [IOB]) and the genera Bacillus, Sulfurimonas, Syntrophobacter and Desulfobacter (sulfur oxidizing bacteria [SOB]) were identified. In the second phase, established after immersion for 7 days, the high amount of EPS inhibited the access of oxygen and promoted the growth of anaerobic bacteria, which were the genus Shewanella (iron-reducing bacterium [IRB]) and the genera Desulfovirga, Desulfovibrio, Desulfuromusa, Desulfococcus, and Desulfosarcina (sulfate-reducing bacteria [SRB]). Electrochemical measurements showed that in the first stage, the aerobic bacteria and the high amount of EPS delayed the cathodic reduction of oxygen. However, in the second stage, EPS and the anaerobic bacteria promoted anodic dissolution.